CHRONIC OBSTRUCTIVE PULMONARY DISEASE: PHARMACOEPIDEMIOLOGICAL STUDY OF ANTIBIOTICS IN THE PERIOD OF EXAGENCE - Olim Siddikov (Scholar Express Journals, 2023)
Chronic obstructive pulmonary disease (COPD) is one of the main causes of death. The risk of death in patients with chronic obstructive pulmonary disease increases depending on the number of cases of exacerbations. Airway obstruction, characteristic of chronic obstructive pulmonary disease, is often aggravated and is associated with a chronic inflammatory reaction. According to the data presented by S. N. Avdeev, 4 biological clusters cause exacerbation of chronic obstructive pulmonary disease: bacterial (11%), eosinophilic (24%), viral (34%), weakly inflammatory (11%). The body reacts to toxins produced by pathogenic microorganisms with an inflammatory reaction, which leads to an exacerbation and a severe course of the disease. The presence of a bacterial factor in the exacerbation of chronic obstructive pulmonary disease requires antibacterial therapy. We studied both from an epidemiological and pharmacoepidemiological point of view and analyzed 788 case histories of patients treated in January- December 2020 in the therapeutic department of the multidisciplinary clinic of Samarkand State Medical University. When analyzing the sensitivity of microorganisms to antibacterial drugs (by the diskdiffuse method, depending on the diameter (mm) in the zone of macroorganism growth suppression based on Sanepidnadzor standards), the following data were revealed: to cefazolin - 65.9%, levofloxacin - 1.7%, cefepime - 3.3%, ceftriaxone - 1.3%. Based on the literature data and the data of our own research, it is advisable to use the drug ceftriaxone from the group of cephalosporins, which is associated with a low resistance of the main pathogens of chronic obstructive pulmonary disease. Irrational dosing, reducing the dose of antibacterial drugs below the doses specified in local and international guidelines and standards, reducing the duration of treatment can cause the development of resistance of microorganisms.
Keywords: COPD; pharmacoepidemiology; cephalosporins; optimization